Changes in behavioural response of Mediterranean seabass (Dicentrarchus labrax L.) under different feeding distributions - Daniela Campobello; Gianfranco Martino; Angelo Olivieri; Gianluca Sarà (Italian Journal of Animal Science, 2010)
Captive-induced behavioural deviations may involve many aspects of fish behaviour such as swimming activity and enhancement of individual aggressiveness. We studied seabass (Dicentrarchus labrax) behaviour as a function of manual and automatic feeding distribution modes. Under manual mode, the food is distributed over an extended area for a longer period, and its precise location is not always predictable, while with pneumatic automatic feeders, fish receive the same amount of resource, which is concentrated in the same surface area over a shorter period. We compared seabass behaviour under automatic and manual conditions collecting video image recordings before, during, and after feeding distribution, in the morning and in afternoon, on two different days, and analysing data within independent sessions of measurements. Feeding modes significantly affected swimming behaviour: automaticallyfed fish were characterised by vertical movements through the water column (towards the surface and bottom) and by horizontal swimming. Manually-fed fish were instead characterised by sharp direction changes during their swimming, mostly towards the surface. Feeding distribution induced changes in collision frequency and elicited aggressive behaviour. In particular, agonistic behaviour (i.e. a fish attacks another fish) was almost exclusively recorded during the feeding under automatic distribution, whereas it was constantly expressed during all the distribution phases under manual mode.